Development of massive multilevel molecular dynamics simulation program, Platypus (PLATform for dYnamic Protein Unified Simulation), for the elucidation of protein functions - Takano, Yu (Journal of computational chemistry, 2016)
© 2016 The Authors. Journal of Computational Chemistry Published by Wiley Periodicals, Inc.